Chapter 26: Wave Properties of Particle - Saifful Kamaluddin, Muzakir (SAP Publications Sdn. Bhd., 2011)
It is known that a particle is one with mass and velocity. However, for an electron, besides having mass and velocity, it also behaves like wave. Electrons in electron microscopy probe are used as ‘light source’ and show diffraction effect of electron just like light.